Measurement of the ratio of b quark production cross sections in (p)over-bar-p collisions at root s=630 GeV and root s=1800 GeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
We report a measurement of the ratio of the bottom quark production cross section in antiproton-proton collisions at √s = 630 GeV to 1800 GeV using bottom quarks with transverse momenta greater than 10.75 GeV identified through their semileptonic decays and long lifetimes. The measured ratio σ(630)/σ(1800) = 0.171±.024±.012 is in good agreement with next-to-leading order quantum chromodynamics. © 2002 The American Physical Society.